2009
DOI: 10.1182/blood.v114.22.1679.1679
|View full text |Cite
|
Sign up to set email alerts
|

R2: Preliminary Results of a Phase II Study of Lenalidomide and Rituximab in Relapsed / Refractory Indolent Non-Hodgkin's Lymphoma (NHL).

Abstract: 1679 Poster Board I-705 Background Lenalidomide (Revlimid®) is a potent immunomodulatory agent that has recently demonstrated clinical activity in the treatment of relapsed/refractory Multiple Myeloma and low- and int-1 risk Myelodysplastic syndromes with the del (5q) mutation. Laboratory data has shown that lenalidomide enhances T- and NK-cell mediated immune synapse formation and ADCC, and it exerts antiproliferative activity. In relapsed/ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…89 After promising single-agent activity was seen particularly in patients with refractoriness to prior therapies, 90 lenalidomide was combined with rituximab and achieved high response rates in first-line therapy. 91,92 An international prospective randomized phase III trial (RELEVANCE) currently compares the so-called R 2 combination of lenalidomide and rituximab against conventional R-chemotherapies, both arms being followed by a respective maintenance in remission.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…89 After promising single-agent activity was seen particularly in patients with refractoriness to prior therapies, 90 lenalidomide was combined with rituximab and achieved high response rates in first-line therapy. 91,92 An international prospective randomized phase III trial (RELEVANCE) currently compares the so-called R 2 combination of lenalidomide and rituximab against conventional R-chemotherapies, both arms being followed by a respective maintenance in remission.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…Combination studies have shown additional benefits in the post‐transplantation setting for aggressive NHL. Preclinical studies have demonstrated synergistic activity between lenalidomide and rituximab (Hernandez‐Ilizaliturri et al , ; Reddy et al , ; Wu et al , ), and emerging clinical data support the potential combination of lenalidomide with a rituximab‐containing regimen in NHL (Dutia et al , ; Czuczman & Rummel, ; Nowakowski et al , ). There is a recent report of a phase II study of 45 patients with newly diagnosed CD20+ DLBCL or FL grade 3 who received standard dose R‐CHOP21 with oral lenalidomide 25 mg/d (days 1–10), which demonstrated an ORR of 98–83% CR (Nowakowski et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Lenalidomide (phase 3 combination trials with monoclonal antibody and chemoimmunotherapy) is used as immunomodulatory drugs [ 18 ]. The immune checkpoint inhibitors used are ipilimumab (CTLA-4 inhibitor, phase I completed and combination trial considered) [ 19 ], pidilizumab, nivolumab, MK-3475 (PD-1 inhibitors, phase 2 single agent and combination trials) [ 20 ].…”
Section: Follicular Lymphoma and Microenvironmentmentioning
confidence: 99%